15th Euromicro Conference on Real-Time Systems, 2003. Proceedings.
DOI: 10.1109/emrts.2003.1212747
|View full text |Cite
|
Sign up to set email alerts
|

Issues in mapping HRT-HOOD to UML

Abstract: HRT-HOOD has methodological strengths that deserve to be preserved in the face

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Instead, they can be viewed as direct corollaries of it in any supporting design methodology (e.g. : HRT-HOOD [2] and derivatives [6,7]) which aims to warrant verifiability by construction, without requiring the use of exceedingly complex analysis techniques. Hence, the two additional restrictions arguably belong in the Ravenscar application domain.…”
Section: Problem Outlinementioning
confidence: 99%
“…Instead, they can be viewed as direct corollaries of it in any supporting design methodology (e.g. : HRT-HOOD [2] and derivatives [6,7]) which aims to warrant verifiability by construction, without requiring the use of exceedingly complex analysis techniques. Hence, the two additional restrictions arguably belong in the Ravenscar application domain.…”
Section: Problem Outlinementioning
confidence: 99%
“…Many design methodologies for real-time systems have been proposed in the literature. One of the most popular is HRT-HOOD [3], which has been recently extended to UML [9]. A system is specified as a set of active, protected or pas-sive objects, and it can be analyzed with classical fixed priority schedulability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, use experience has shown that reallife design does not rigidly follow the top-down approach entailed by hierarchical decomposition, but it has very distinct bottom-up connotations, whereby objects are also aggregated a posteriori. This notion, which HRT-UML promotes [13], suggests that the HRT type of a parent object is determined by (as opposed to determines) the HRT type of its child objects. Any aggregate of HRT-UML objects may be defined at design time as a single-parent by promoting (segments of) the provided interface of its internal objects to the parent interface.…”
Section: Hrt-uml and The Ravenscar Profilementioning
confidence: 99%
“…HRT-UML [13,21] is the result of a project that is to transpose, by a thorough balance of preservation and extension, the HRT-HOOD design method [6] on the UML meta-model [15,14]. A prototype tool-set currently exists, which we have equipped with the proposed code generation engine.…”
Section: Introductionmentioning
confidence: 99%